Correction: Tao et al. Development of a Label-Free Electrochemical Aptasensor for the Detection of Tau381 and its Preliminary Application in AD and Non-AD Patients’ Sera. Biosensors 2019, 9, 84 - Dan Tao; Bingqing Shui; Yingying Gu; Jing Cheng; Weiying Zhang; Nicole Jaffrezic-Renault; Shizhen Song; Zhenzhong Guo (Biosensors)
In the original publication [...]